Grey Wolf optimization based improved protection of wind power generation systems - Rezaei N.; Nasir Uddin M.; Khairul Amin I.; Lutfi Othman M.; Abidin I.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power generation; Electric power system interconnection; Electric relays; Electric utilities; IEEE Standards; Wind power; Intelligent Algorithms; Nonlinear characteristics; Optimization techniques; Overcurrent relays; Power system protection; Relay coordination; Wind farm; Wind power generation systems; Electric power system protection